Effect of green tea on the second degree burn wounds in rats - Mohammad Javad Fatemi; Babak Nikoomaram; Amir Asadollah Khajeh Rahimi; Donya Talayi; Shahrzad Taghavi; Yaser Ghavami (Indian Journal of Plastic Surgery)
Background: Various studies indicate that the green tea has anti-inflammatory and anti-oxidative properties. Moreover, a few studies have been carried out that demonstrate beneficial effects of green tea on burned patients. Materials and Methods: In this study, green tea, Vaseline, and silver sulfadiazine dressings were used as first-aid treatment to deep dermal contact burns in rats, compared with a control of nothing. After creating second-degree burn on the dorsum of rats, the treatments were applied for 15 min in four groups. Wound dressing changes were daily. Macroscopic study was performed on days 1, 3, 7, and 14 by using a digital camera and software processing of photos. Microscopic examination was done by pathologic evaluation of skin specimens on day 14. Results: We observed that green tea usage significantly decreased burn size in comparison to the control group (P = 0.004). Conclusion: Green tea is effective on healing process of second degree burn wounds.